BERMAIN DAN BERINTERAKSI DENGAN AMERICAN NATIVES SEBAGAI METODE BELAJAR ANAK DI KEDIRI, JAWA TIMUR - Ika Silviana; Fatma Puri Sayekti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
Reading parks or public library generally offer the focal point of literacy activities with the encouragement of people reading interest. These activities undertaken by providing a reading room and socializing the importance of reading. This social service along with Taman Baca Puri Anjali, located in Kaliombo, Kediri, East Java, observes the problems related to learning methods, especially in reading, that occur in children. Through the activity titled “Kids, Are You Ready to Talk to American Native?” together create learning activities by playing, based on Paulo Freire’s method, conscientizacao. This activity invites children to learn English directly with people who use English language in their daily life, named American natives. It has a happy learning effect on children and they feel that learning English is easier than before. They also assimilate a more varied pattern of literacy, without leaving the books that become the world’s window for learners.